Gender aspects of incidence of antibody-mediated rejection and allograft vasculopathy events after heart transplantation - N. N. Koloskova; V. N. Poptsov; V. М. Zakharevich; I. I. Muminov; N. P. Mozheyko; O. E. Gichkun; Е. А. Nikitina; V. S. Cvan; T. A. Khalilulin; A. R. Zakiryanov; A. O. Shevchenko (Вестник трансплантологии и искусственных органов)
Abstract. Despite improvements in immunosuppressive therapy, antibody-mediated rejection (AMR) remains one of the most important risk factors for poor prognosis for survival of recipients, cardiac graft dysfunction, and cardiac allograft vasculopathy (CAV) after heart transplantation.Aim: to assess the incidence of case of antibodymediated rejection and cardiac allograft vasculopathy depending on the gender of the patients who underwent heart transplantation in our Center from January 2010 to December 2017.Methods. The median observation was 42 months. The study comprised 606 patients (84 [14%] women) who underwent heart transplantation in 2010 to 2017. We analyzed all the episodes of antibody-mediated rejection, which were diagnosed by the results of endomyocardial biopsies.Results. We comparing the total incidence of antibody-mediated rejection and we are found significant differences among men and women who underwent heart transplantation (p < 0.05), the survival rate during the first year after heart transplantation was 95 and 92%, respectively. The incidence of antibody-consistent rejection was significantly higher among women who had a history of pregnancy and/or use of mechanical circulatory support systems (UNOS status 1A) in the pre-transplantation history (p < 0.05), and we also found significant differences in the incidence of cardiac allograft vasculopathy in women diagnosed with AMR (p < 0.05). The survival rate among women within a year after the diagnosis of AMR is 83% compared to 96% of the recipients free from AMR.Conclusions. Women are at higher risk for AMR after heart transplantation and it increases their risk for cardiac allograft vasculopathy. Females recipients may more frequent myocardial control biopsies and a personalized approach in prescribing immunosuppressive therapy. Women-recipients of transplanted heart should undergo These measures will help to identify in time the development of antibodymediated rejection and reduce the incidence of cardiac allograft vasculopathy after heart transplant.